2008
DOI: 10.1504/ijmic.2008.021000
|View full text |Cite
|
Sign up to set email alerts
|

State estimation for non-linear systems using a decoupled multiple model

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 30 publications
0
34
0
Order By: Relevance
“…In the sequel, this multiple model is called the heterogeneous multiple model. The previously quoted works have illustrated successful implementations of this structure for modelling (Venkat et al, 2003;Vinsonneau et al, 2005;Orjuela et al, 2006), control (Gawthrop, 1995;Gatzke and Doyle III, 1999;Gregorčič and Lightbody, 2000) or state estimation and diagnostic (Kanev and Verhaegen, 2006;Uppal et al, 2006;Orjuela et al 2008;2009) and have shown its relevance. Hence, this kind of multiple model can be used as an interesting alternative to the homogeneous multiple model.…”
Section: R Orjuela Et Almentioning
confidence: 99%
“…In the sequel, this multiple model is called the heterogeneous multiple model. The previously quoted works have illustrated successful implementations of this structure for modelling (Venkat et al, 2003;Vinsonneau et al, 2005;Orjuela et al, 2006), control (Gawthrop, 1995;Gatzke and Doyle III, 1999;Gregorčič and Lightbody, 2000) or state estimation and diagnostic (Kanev and Verhaegen, 2006;Uppal et al, 2006;Orjuela et al 2008;2009) and have shown its relevance. Hence, this kind of multiple model can be used as an interesting alternative to the homogeneous multiple model.…”
Section: R Orjuela Et Almentioning
confidence: 99%
“…It describes nonlinear behaviors while having a structure based on linear models allowing the extension of some tools from the linear domain to the nonlinear one. Using identification , linearization , or the so‐called sector nonlinearity transformation , a T‐S model for the system can be obtained under the following form: {ẋ(t)=i=1rμi(ξ(t))Aix(t)+Biu(t)+Eid(t)y(t)=i=1rμi(ξ(t))Cix(t)+Gid(t)+f(t) where AiI-1.6331ptRn×n,BiI-1.6331ptRn×m,CiI-1.6331ptRp×n,Eidouble-struckRn×nd, and Gidouble-struckRp×nd are the matrices describing the so‐called i t h sub‐model. The integer r represents the number of sub‐models.…”
Section: Takagi–sugeno Modelingmentioning
confidence: 99%
“…The function F is a continuous and infinitely differentiable nonlinear function and E is a singular matrix with constant parameters and rank(E)=r < n. The dynamic behavior of this nonlinear system can b e characterized by a coupled Takagi-Sugeno [15] representation composed by several local linear models. So, based on Taylor series expansion of the smooth nonlinear functions around various operating points (xi, ui), the multi-models representation [14] of (1) is:…”
Section: Multi-models Singular Systemmentioning
confidence: 99%